PENINGKATAN LITERASI NUMERASI MELALUI MEDIA MINIBOOK PERKALIAN PADA SISWA KELAS IV (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aimed to improve numeracy literacy among fourth-grade students through the use of a Multiplication Minibook as an instructional medium. The study was conducted in two cycles following the Kemmis and McTaggart model, which consists of planning, acting, observing, and reflecting stages. The participants were 28 fourth-grade students selected through total sampling. Data were collected through numeracy literacy tests, observation sheets, and documentation. Quantitative analysis included descriptive statistics, N-Gain, normality testing, homogeneity testing, and paired samples t-test. The results showed a significant improvement in students’ numeracy literacy after the implementation of the Minibook. In the first cycle, the average score increased from 21.2 to 27.4 with an N-Gain value of 0.42 in the medium category. Improvements continued in the second cycle, with more than 75% of students achieving mastery. Statistical testing indicated a significant difference between pretest and posttest scores (t = 16.494; p < 0.001), confirming the effectiveness of the Minibook. Observations also revealed increased student engagement, conceptual understanding, and ability to interpret mathematical contexts. Overall, the Multiplication Minibook proved to be an effective and practical medium for enhancing numeracy literacy in elementary school mathematics instruction.